Regioselective chemoenzymatic syntheses of ferulate conjugates as chromogenic substrates for feruloyl esterases - Gherbovet, Olga; Ferreira, Fernando; Clément, Apolline; Ragon, Mélanie; Durand, Julien; Bozonnet, Sophie; O'Donohue, Michael J.; Fauré, Régis (Beilstein Journal of Organic Chemistry, 2021)
Generally, carbohydrate-active enzymes are studied using chromogenic substrates that provide quick and easy color-based detection of enzyme-mediated hydrolysis. For feruloyl esterases, commercially available chromogenic ferulate derivatives are both costly and limited in terms of their experimental application. In this study, we describe solutions for these two issues, using a chemoenzymatic approach to synthesize different ferulate compounds. The overall synthetic routes towards commercially available 5-bromo-4-chloro-3-indolyl and 4-nitrophenyl 5-O-feruloyl-α-ʟ-arabinofuranosides were significantly shortened (from 7 or 8 to 4–6 steps), and the transesterification yields were enhanced (from 46 to 73% and from 47 to 86%, respectively). This was achieved using enzymatic (immobilized Lipozyme® TL IM from Thermomyces lanuginosus) transesterification of unprotected vinyl ferulate to the primary hydroxy group of α‐ʟ‐arabinofuranosides. Moreover, a novel feruloylated 4-nitrocatechol-1-yl-substituted butanetriol analog, containing a cleavable hydroxylated linker, was also synthesized in 32% overall yield in 3 steps (convergent synthesis). The latter route combined the regioselective functionalization of 4-nitrocatechol and enzymatic transferuloylation. The use of this strategy to characterize type A feruloyl esterase from Aspergillus niger reveals the advantages of this substrate for the characterizations of feruloyl esterases.
Keywords: esterase; feruloylated conjugates; hydrolysis; lipase; transesterification